Editorial Perspective: Psychological stress and epigenetic aging – what can we learn and how can we prevent?. (June 2016) - Zannas, Anthony S.
Abstract : Psychological stress can exert a lasting impact on the aging process. This hypothesis, long posited by Hans Selye, has been supported by evidence linking stressors with several aging‐related disease phenotypes. However, little is known about the molecular mechanisms underlying this association. Among plausible mechanisms linking stress and aging, evidence supports the role of epigenetic modifications, a set of molecular processes that can be induced by environmental stressors and regulate gene expression without altering the underlying genetic sequence. In particular, recent evidence shows that psychological stress can accelerate epigenetic aging, a measure based on DNA methylation prediction of chronological age that shows promise as biomarker of aging. Some studies further suggest that epigenetic aging could be modifiable, albeit others contradict this hypothesis. Future studies will need to determine the preventability or reversibility of epigenetic aging in response to distinct interventions and the potential clinical implications of such a prevention or reversal.